Adaptasi Ekologis Masyarakat Nelayan Pesisir Sungsang, Kecamatan Banyuasin II, Kabupaten Banyuasin, Sumatera Selatan - Eva Lidya; Yusnaini Yusnaini; Yunindyawati Yunindyawati; Alamsyah Alamsyah (Jurnal Empirika, 2017)
This research aim to (1) identify ecological problems affected by climate change on marine ecosystem and the life of coastal communities, and (2) to analyze the pattern of ecological adaptation of fishermen deal with the impact of climate change. This research uses qualitative method completed with literature review. Primary data collection is done through in-dept interview, observation and focus group discussion. The results of this research are (1) there are ecological problems influenced by climate change in the form of high waves of sea water, difficult prediction wind direction, loss of location of fish hordes, pollution of sea water due to palm oil waste and the difficulty of sanitary water. (2) the pattern of community coastal ecological adaptation in the form of change of catching location, change of fishing gear, the strategy of pulling over the valley during the storm, the use of GPS (Global Positioning System), and conducting rainfed.